The impact of U.S. monetary policy on capital flows to emerging market economies - Katia Rocha; Alexis Maka (Institute for Applied Economic Research (ipea), 2022)
This paper examines the potential impact of US monetary policy normalization on portfolio capital flows to Emerging Markets Economies (EME) explicitly taking into account the unconventional US monetary policy. We build an econometric model of the drivers of capital flows to EMEs and the results suggest that Brazil maybe less vulnerable than EMEs to changes in US monetary policy.
Keywords: 330; capital flows; emerging market economies; unconventional US; monetary policy